Analysis of cystic fibrosis gene mutations in children with cystic fibrosis and in 964 infertile couples within the region of Basilicata, Italy: a research study - Dell’Edera, Domenico; Benedetto, Michele; Gadaleta, Gemma; Carone, Domenico; Salvatore, Donatello; Angione, Antonella; Gallo, Massimiliano; Milo, Michele; Pisaturo, Maria Laura; Di Pierro, Giuseppe; Mazzone, Eleonora; Epifania, Annunziata Anna (Journal of medical case reports, 2014)
Cystic fibrosis is the most common autosomal recessive genetic disease in the Caucasian population. Extending knowledge about the molecular pathology on the one hand allows better delineation of the mutations in the CFTR gene and the other to dramatically increase the predictive power of molecular testing. This study reports the results of a molecular screening of cystic fibrosis using DNA samples of patients enrolled from January 2009 to December 2013. Patients were referred to our laboratory for cystic fibrosis screening for infertile couples. In addition, we identified the gene mutations present in 76 patients affected by cystic fibrosis in the pediatric population of Basilicata. In the 964 infertile couples examined, 132 subjects (69 women and 63 men) resulted heterozygous for one of the CFTR mutations, with a recurrence of carriers of 6.85%. The recurrence of carriers in infertile couples is significantly higher from the hypothetical value of the general population (4%). This study shows that in the Basilicata region of Italy the CFTR phenotype is caused by a small number of mutations. Our aim is to develop a kit able to detect not less than 96% of CTFR gene mutations so that the relative risk for screened couples is superimposable with respect to the general population.